PENGARUH CURRENT RATIO (CR) DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PADA PT ADI SARANA ARMADA TBK PERIODE 2014-2023 - Mutia Afriani; Simangunsong, Ria Rosalia (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This research aims to determine This research aims to determine the effect of Current Ratio (CR) and Return On Asset (ROA) on the stock price of PT Adi Sarana Armada Tbk. The method used in this research is multiple linear regression, involving classical assumption tests, followed by partial significance testing using the t-test, while the F-test is used to assess the joint effect. The research results show that the Current Ratio (CR) variable has a significant effect on stock prices. Meanwhile, the Return On Asset (ROA) variables do not have a significant effect on share prices. Simultaneously, the Current Ratio (CR) and Return On Asset (ROA) variables influence stock prices. The adjusted R-squared value in this study is 0,595 , which means that the ability of the independent variable to explain variations in the dependent variable is 59,5% while the remaining 40,5% is explained by other independent variables outside the model.